Knowledge and awareness of hepatitis B among households in Malaysia: a community-based cross-sectional survey - Rajamoorthy, Yogambigai; Mohd Taib, Niazlin; Munusamy, Subramaniam; Anwar, Samsul; Wagner, Abram Luther; Mudatsir, Mudatsir; Müller, Ruth; Kuch, Ulrich; Groneberg, David Alexander; Harapan, Harapan; Khin, Aye Aye (BioMed Central, 2019)
Background: Hepatitis B (HepB) is a major public health concern in Malaysia yet little is known about knowledge and awareness of this infection in the country. Such information is essential for designing effective intervention strategies for HepB prevention and control. The aim of this study was to characterize knowledge and awareness regarding HepB in Malaysia and to identify their associated sociodemographic determinants. Methods: A community-based cross-sectional survey was conducted between January and May 2016 in Selangor state of Malaysia. A two-stage cluster random sampling design was used and one adult member of selected households was interviewed face-to-face. Logistic regression was used to estimate the differences in knowledge and awareness between groups. Results: A total of 764 households completed the interviews and were included in the final analysis. Only 36.9 and 38.8% of the participants had good knowledge and awareness, respectively. The factors associated with good knowledge were being in the 35–44 year age group, Malay ethnicity, high educational attainment and high family income. Being Chinese, being older and having high educational attainment were determinants of having good awareness towards HepB. Participants who had good knowledge were 2.5 times more likely to also have good awareness (OR: 2.41, 95% CI: 1.78–3.26, p < 0.001). Conclusions: This study reveals a low level of knowledge and awareness of HepB among households in Malaysia. This finding highlights the need to improve public knowledge and awareness through well-designed programs targeting vulnerable groups in order to reduce hepatitis B virus transmission and achieve the governmental target of eliminating viral hepatitis as a public health concern by 2030.